PRAXIS: the determining element of innovation behavior in the hospitality industry - Zopiatis, Anastasios; Theocharous, Antonis L. (My University, 2018)
Innovation has emerged as an essential component of organizational success in the 21st century. Nonetheless, empirical research around innovation in the hospitality industry remains limited; especially in relation to small island tourist destinations like Cyprus. Responding to this emerging need, the study investigates the role of human capital – managerial employees (n = 425) – as it relates to innovation initiatives in the hospitality workplace. Three hypotheses are postulated and analyzed using Structural Equation Modeling, a multivariate statistical analysis technique, to broaden conceptual horizons regarding the relationship between perceived organizational innovation culture and support, and the informed innovation-specific actions of employees, as well as their resultant behavior. The results suggest that praxis, which is defined as action informed by theory and experiences, is a vital element of innovation behavior in the hospitality industry. The resultant findings and implications are of interest to both academic and professional stakeholders in hospitality.
Keywords: Praxis; Innovation; Human capital; SEM; Mediation analysis